Enrichment features, ecological risks assessment and quantitative sources appointment of sediment heavy metals: An example of the urbanized Xizhi River catchment, South China - Chao Yan; Qirui Wu; Rui Li; Zuobing Liang; Zaizhi Yang; Aiping Zhu; Lei Gao (Environmental Chemistry and Ecotoxicology)
Rapid industrialization is typically the primary cause for heavy metals [HMs: copper (Cu), zinc (Zn), cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb)] contamination in urbanized river basins. In this study, sediment cores were collected from the Xizhi River (XZR) of the Pearl River Delta, South China, and its tributary, the Danshui River (DSR), to analyze the total concentrations and geochemical fractions of these HMs and to assess their potential hazards to the river ecosystem. By integrating a traditional geochemical model and multivariate statistical analysis into a positive matrix factorization (PMF) method, we quantitatively identified the possible sources of HM contamination in the sediments. The total concentrations of sediment HMs distinctly exceeded local background values and were higher in the DSR compared to the XZR. The enrichment levels of HMs were influenced not only by sediment properties, such as texture, but also, more critically, by the distribution of contamination sources. Sediment Cu, Zn, Cd, and Ni were dominated by acid-soluble fractions (31.4–56.2 %), exhibiting a great mobility potential; while reducible and oxidizable fractions were the predominant geochemical forms for Pb (45.0 ± 12.8 %) and Cr (37.3 ± 7.09 %). Based on the geo-accumulation index and enrichment factor of individual metals, contamination levels decreased in the order of Cd > Cu, Zn, and Ni > Cr and Pb. Sediment Cd was identified as the major contributor to the potential ecological risks posed to aquatic species. Across the entire watershed, the main sources of HM contamination were identified as industrial effluents (54 %), agrochemicals (16 %), domestic sewage (14 %), and weathering of parent rocks (16 %).